High-flame-retardant waste spinning felt and production process thereof

Through the processing of modified treatment and modified chain expansion, amino nano -nano -nano nanosilicon, and second -second aluminosphop phosphate, the nylon scraps of nylon scrap flame retardant performance and mechanical properties were solved. It realizes high flame retardant performance and good mechanical properties.

CN119372841AActive Publication Date: 2025-01-28ANHUI JIELIANG NEW MATERIALS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411277864.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-28
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

The flame retardant and mechanical properties of nylon waste spinning felt are reduced during processing, and are flammable, resulting in safety hazards.

Method used

By immersion in pre -treated nylon waste spinning fiber in isopropanol and chlorolytic acid solution for modification, increase the activity site; then materials such as modified chain expansion, amino nano nanoxide, and aluminum phosphates of the second and second -second aluminum phosphates Together, molten spinning and thermal pressure treatment to form high flame -retardant waste spinning felt.

Benefits of technology

It significantly improves the flame retardant and mechanical properties of waste spinning felt, reduces the release of combustible gas, enhances the tear resistance, and reduces flames.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005040771910000081
    Figure BDA0005040771910000081
  • Figure BDA0005040771910000091
    Figure BDA0005040771910000091
Patent Text Reader

Abstract

The invention discloses a high-flame-retardant waste spinning felt and a production process thereof, and belongs to the technical field of waste spinning felt materials.The production process comprises the following steps that S1, nylon waste spinning is subjected to recycling, sorting and disinfection and then subjected to opening and carding, and pretreated fibers are obtained; s2, the pretreated fibers are soaked in an isopropanol solution, then a chloroacetic acid solution with the concentration being 10 wt% is added, stirring reaction is conducted for 1-1.5 h at the temperature of 50-60 DEG C, then washing is conducted through deionized water, drying is conducted, and modified fibers are obtained; s3, uniformly mixing the modified fibers, the modified chain extender, amino nano silicon dioxide and aluminum diethylhypophosphite, adding the mixture into a melt spinning machine for spinning, carding, paving to form a net, and then performing needling processing and hot-pressing treatment to obtain the high-flame-retardant waste spun felt. The nylon waste spinning is used as a base material, and under the synergistic effect of the modified chain extender, the amino nano silicon dioxide and the flame retardant, the tear resistance and flame retardance of the waste spinning felt are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of waste spun felt material preparation, and in particular relates to a highly flame-retardant waste spun felt and a production process thereof. Background Art

[0002] With the enhancement of environmental awareness and the popularization of the concept of resource recycling, the recycling and reuse of waste textiles has become a hot issue of global concern. Nylon fiber, as a wear-resistant and non-toxic synthetic fiber, is widely used in the textile field. While meeting market demand, it also produces a large amount of waste textiles. Therefore, nylon waste can be recycled and processed into felt to improve resource utilization. However, nylon waste is a flammable material, which will produce molten droplets and toxic gases during the combustion process, posing a huge threat to people's lives and property safety.

[0003] In the prior art, aluminum diethylphosphinate is usually added during the preparation of nylon textiles to improve the flame retardant properties of nylon textiles. As a phosphite flame retardant, aluminum diethylphosphinate is widely used in gas phase flame retardancy and condensed phase flame retardancy and has excellent flame retardant properties. However, during the melt spinning process of nylon waste modified with aluminum diethylphosphinate, on the one hand, due to the repeated recycling and processing of nylon waste, the molecular chain of nylon waste is broken, resulting in reduced flame retardant properties and mechanical properties. On the other hand, aluminum diethylphosphinate is oxidized by heat to form aluminum phosphate derivatives, which react with the terminal carboxyl groups of the nylon waste molecular chains, further promoting the degradation of nylon waste, generating more combustible gases, and making nylon waste felt easily ignited. Therefore, how to improve the flame retardant properties and mechanical properties of waste felt is a technical problem that needs to be solved at present. Summary of the invention

[0004] The object of the present invention is to provide a highly flame-retardant waste spun felt and a production process thereof, so as to solve the problems in the background technology.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A production process of highly flame-retardant waste spun felt comprises the following steps:

[0007] S1, recovering, sorting, and disinfecting nylon waste, and then opening and combing the waste to obtain pretreated fibers;

[0008] S2, immersing the pretreated fiber in a 90wt% isopropanol solution, then adding a 10wt% chloroacetic acid solution, stirring and reacting at 50-60°C for 1-1.5h, and then washing with deionized water and drying to obtain a modified fiber; the pretreated fiber is immersed in chloroacetic acid to obtain a modified fiber with carboxyl groups grafted on the surface, thereby increasing the number of active sites on the surface of the modified fiber containing terminal amino groups and terminal carboxyl groups;

[0009] S3. The modified fiber, modified chain extender, amino nano-silica and diethylaluminum hypophosphite are uniformly mixed and added into a melt spinning machine for spinning. After combing and laying into a net, the fibers are needle punched and hot pressed to obtain highly flame-retardant waste spun felt.

[0010] Furthermore, the weight ratio of the pretreated fiber, the isopropanol solution, and the chloroacetic acid solution is 100-120:500-600:30-60.

[0011] Furthermore, the weight ratio of the modified fiber, the modified chain extender, the amino nano-silica, and the diethylaluminum hypophosphite is 90-110:8-11:0.5-3:6-8.

[0012] Further, the modified chain extender is prepared by the following steps:

[0013] A1. Add 3,4-dihydroxybenzaldehyde to anhydrous methanol, stir and mix, add 1,3-bis(3-aminopropyl)tetramethyldisiloxane alcohol solution dropwise, control the dropping time to 20-30 min, then add glacial acetic acid and anhydrous magnesium sulfate, stir and react for 9-10 h in a nitrogen atmosphere at 60-70° C., cool and place in ice deionized water for precipitation, filter, wash and dry to obtain a silicon-containing Schiff base; use anhydrous formaldehyde as solvent, glacial acetic acid as catalyst and anhydrous magnesium sulfate as water absorbent, react the aldehyde group of 3,4-dihydroxybenzaldehyde with the amino group in 1,3-bis(3-aminopropyl)tetramethyldisiloxane to obtain a silicon-containing Schiff base;

[0014] A2. Add silicon-containing Schiff base and potassium hydroxide to anhydrous ethanol, stir and mix, add epichlorohydrin, stir and react for 3-4 hours under nitrogen atmosphere at 60-70° C., cool to room temperature, dropwise add a 40wt% potassium hydroxide aqueous solution, control the dropping time to 0.5-1h, and after the dropwise addition is completed, stir and react for 5-6h at 50-60° C., and then post-treat to obtain a modified chain extender; using potassium hydroxide as a catalyst, a phenolic hydroxyl group on the silicon-containing Schiff base is substituted with the chlorine on the epichlorohydrin to obtain a modified chain extender containing an epoxy group and an organosilicon segment, and at the same time, an additional potassium hydroxide aqueous solution is used to neutralize the hydrogen chloride generated during the reaction.

[0015] Furthermore, the dosage ratio of the anhydrous methanol, 3,4-dihydroxybenzaldehyde, 1,3-bis(3-aminopropyl)tetramethyldisiloxane alcohol solution, glacial acetic acid and anhydrous magnesium sulfate is 90mL:4-6g:18-20mL:0.5-1mL:0.6g; the 1,3-bis(3-aminopropyl)tetramethyldisiloxane alcohol solution is prepared by dissolving 1-3mL 1,3-bis(3-aminopropyl)tetramethyldisiloxane in 20mL anhydrous methanol.

[0016] Furthermore, the usage ratio of the anhydrous ethanol, the silicon-containing Schiff base, the potassium hydroxide, the epichlorohydrin and the potassium hydroxide aqueous solution is 60 mL: 3-6 g: 0.6 g: 4-8 mL: 4 mL.

[0017] Furthermore, the post-treatment is to cool to room temperature, filter using a Buchner funnel, and then perform rotary evaporation, dissolve in dichloromethane, and wash with a saturated sodium carbonate aqueous solution and deionized water in sequence, and then perform rotary evaporation again.

[0018] Furthermore, the amino nano-silica is prepared by the following steps:

[0019] Add nano-silica to deionized water, perform ultrasonic dispersion for 30 minutes, add 3-aminopropyltriethoxysilane, stir and mix, add PBS buffer to adjust the pH value to 7-8, stir and react at 60-70°C for 10-12 hours, and obtain amino nano-silica after centrifugation, washing and drying; the hydroxyl groups generated by hydrolysis of the 3-aminopropyltriethoxysilane molecular chain and the hydroxyl groups on the surface of the nano-silica are dehydrated and condensed to obtain amino nano-silica containing amino modification.

[0020] Furthermore, the usage ratio of the deionized water, nano-silicon dioxide and 3-aminopropyltriethoxysilane is 40 mL: 1-4 g: 1-3 mL.

[0021] A highly flame-retardant waste spun felt is prepared by the above production process.

[0022] Beneficial effects of the present invention:

[0023] The amino nano-silica of the present invention is used as a synergistic flame retardant. When blended with modified fibers, it can combine with the carboxyl groups in the molecular chains of the modified fibers through the amino groups to form amide bonds, thereby improving the compatibility of the amino nano-silica with the modified fibers. When the waste felt encounters a heat source and burns, the modified nano-silica on the molecular chains of the waste felt can not only form a network structure of Si-OS i, effectively inhibiting the formation of molten droplets, but also promote the effect of complete combustion, reduce the release of carbon monoxide and black smoke, increase the release of carbon dioxide, and improve the flame retardant effect. At the same time, aluminum diethylphosphinate can form a carbon layer on the surface of the waste felt, and synergize with the amino nano-silica to promote cross-linking and carbonization to form a dense heat-insulating layer, effectively reducing the volatilization of combustible gases. In addition, aluminum diethylphosphinate decomposes to produce phosphorus-containing free radicals such as PO2· and PO·, which can effectively capture active free radicals in the gas phase when the waste felt is burned, thereby terminating the chain reaction in the combustion process. Under the synergy of the two, the flame retardant performance of the waste felt is further enhanced.

[0024] The present invention uses nylon waste as a base material, and introduces a modified chain extender containing an epoxy group and a Schiff base. When blended with the modified fiber, on the one hand, the epoxy group can undergo a coupling reaction with the terminal amino group and the terminal carboxyl group on the modified fiber molecular chain to promote chain growth, and can reconnect the modified fiber molecular chain broken during the processing process, thereby improving the strength and tensile properties of the re-spun fiber and enhancing the tear resistance of the waste felt. On the other hand, the nitrogen atom on the imine in the Schiff base can coordinate with the metal center in the aluminum phosphate derivative generated when diethyl aluminum phosphinate is heated to form a complex, thereby effectively inhibiting the degradation behavior of the aluminum phosphate derivative on the modified fiber, avoiding the generation of combustible gas, and reducing the ignition susceptibility of the waste felt. At the same time, the modified chain extender contains an organic silicon segment, which is not only flexible but also flame retardant, thereby further improving the flame retardant properties of the waste felt. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] This embodiment provides a modified chain extender, which is prepared by the following steps:

[0028] A1. Add 1 mL of 1,3-bis(3-aminopropyl)tetramethyldisiloxane to 20 mL of anhydrous methanol to obtain a 1,3-bis(3-aminopropyl)tetramethyldisiloxane alcohol solution;

[0029] A2. Add 4 g of 3,4-dihydroxybenzaldehyde to 90 mL of anhydrous methanol, stir and mix, add dropwise 18 mL of 1,3-bis(3-aminopropyl)tetramethyldisiloxane alcohol solution, control the dropping time to 20 min, then add 0.5 mL of glacial acetic acid and 0.6 g of anhydrous magnesium sulfate, stir and react for 9 h under a nitrogen atmosphere at 60 ° C, cool and place in ice deionized water for precipitation, filter, wash and dry to obtain a silicon-containing Schiff base;

[0030] A3. Add 3g of silicon-containing Schiff base and 0.6g of potassium hydroxide to 60mL of anhydrous ethanol, stir and mix, add 4mL of epichlorohydrin, stir and react for 3h under nitrogen atmosphere and 60°C, cool to room temperature, drop 4mL of 40wt% potassium hydroxide aqueous solution, control the dropping time to 0.5h, after the dropwise addition, stir and react for 5h at 50°C, cool to room temperature, filter with a Buchner funnel, and then dissolve in 60mL of dichloromethane after rotary evaporation, wash with saturated sodium carbonate aqueous solution and deionized water in turn, and then rotary evaporation to obtain a modified chain extender.

[0031] Example 2

[0032] This embodiment provides a modified chain extender, which is prepared by the following steps:

[0033] A1. Add 2 mL of 1,3-bis(3-aminopropyl)tetramethyldisiloxane to 20 mL of anhydrous methanol to obtain a 1,3-bis(3-aminopropyl)tetramethyldisiloxane alcohol solution;

[0034] A2. Add 5 g of 3,4-dihydroxybenzaldehyde to 90 mL of anhydrous methanol, stir and mix, add dropwise 19 mL of 1,3-bis(3-aminopropyl)tetramethyldisiloxane alcohol solution, control the dropping time to 25 min, then add 0.8 mL of glacial acetic acid and 0.6 g of anhydrous magnesium sulfate, stir and react under nitrogen atmosphere at 65 ° C for 9.5 h, cool and place in ice deionized water for precipitation, filter, wash and dry to obtain a silicon-containing Schiff base;

[0035] A3. Add 4 g of silicon-containing Schiff base and 0.6 g of potassium hydroxide to 60 mL of anhydrous ethanol, stir and mix, add 6 mL of epichlorohydrin, and stir and react for 3.5 h under a nitrogen atmosphere and 65 ° C. After cooling to room temperature, add 4 mL of a 40 wt% potassium hydroxide aqueous solution dropwise, and control the addition time to 0.8 h. After the addition is complete, stir and react at 55 ° C for 5.5 h. After cooling to room temperature, filter using a Buchner funnel, and then after rotary evaporation, dissolve in 60 mL of dichloromethane, and wash with a saturated sodium carbonate aqueous solution and deionized water in turn, and then rotary evaporate to obtain a modified chain extender.

[0036] Example 3

[0037] This embodiment provides a modified chain extender, which is prepared by the following steps:

[0038] A1. Add 3 mL of 1,3-bis(3-aminopropyl)tetramethyldisiloxane to 20 mL of anhydrous methanol to obtain a 1,3-bis(3-aminopropyl)tetramethyldisiloxane alcohol solution;

[0039] A2. Add 6 g of 3,4-dihydroxybenzaldehyde to 90 mL of anhydrous methanol, stir and mix, add 20 mL of 1,3-bis(3-aminopropyl)tetramethyldisiloxane alcohol solution dropwise, control the dropping time to 30 min, then add 1 mL of glacial acetic acid and 0.6 g of anhydrous magnesium sulfate, stir and react for 10 h under a nitrogen atmosphere at 70 ° C, cool and place in ice deionized water for precipitation, and then filter, wash and dry to obtain a silicon-containing Schiff base;

[0040] A3. Add 6 g of silicon-containing Schiff base and 0.6 g of potassium hydroxide to 60 mL of anhydrous ethanol, stir and mix, add 8 mL of epichlorohydrin, stir and react for 4 h under a nitrogen atmosphere at 70 ° C, cool to room temperature, drop 4 mL of a 40 wt% potassium hydroxide aqueous solution, control the dropping time to 1 h, after the dropwise addition is completed, stir and react at 60 ° C for 6 h, cool to room temperature, filter using a Buchner funnel, and then after rotary evaporation, dissolve in 60 mL of dichloromethane, and wash with a saturated sodium carbonate aqueous solution and deionized water in turn, and then rotary evaporate to obtain a modified chain extender.

[0041] Example 4

[0042] This embodiment provides an amino nano-silica, which is prepared by the following steps:

[0043] Add 1 g of nano-silica to 40 mL of deionized water, ultrasonically disperse for 30 min, add 1 mL of 3-aminopropyltriethoxysilane, stir and mix, add PBS buffer to adjust the pH value to 7, stir and react at 60°C for 10 h, and then centrifuge, wash and dry to obtain amino nano-silica.

[0044] Example 5

[0045] Add 2 g of nano-silica to 40 mL of deionized water, ultrasonically disperse for 30 min, add 1.5 mL of 3-aminopropyltriethoxysilane, stir and mix, add PBS buffer to adjust the pH value to 7.5, stir and react at 65 ° C for 11 h, and then centrifuge, wash and dry to obtain amino nano-silica.

[0046] Example 6

[0047] 4 g of nano-silica was added to 40 mL of deionized water, and ultrasonic dispersion was performed for 30 min. 3 mL of 3-aminopropyltriethoxysilane was added, and the mixture was stirred and mixed. PBS buffer was added to adjust the pH value to 8, and the mixture was stirred and reacted at 70° C. for 12 h. After centrifugation, washing, and drying, amino nano-silica was obtained.

[0048] Example 7

[0049] This embodiment provides a production process of highly flame-retardant waste spun felt, comprising the following steps:

[0050] S1, recovering, sorting, and disinfecting nylon waste, and then opening and combing the waste to obtain pretreated fibers;

[0051] S2, immersing 100 parts by weight of the pretreated fiber in 500 parts by weight of a 90 wt% isopropanol solution, adding 30 parts by weight of a 10 wt% chloroacetic acid solution, stirring and reacting at 50° C. for 1 hour, and then washing with deionized water and drying to obtain a modified fiber;

[0052] S3. Evenly mix 90 parts by weight of modified fiber, 8 parts by weight of modified chain extender, 0.5 parts by weight of amino nano-silica and 6 parts by weight of diethylaluminum hypophosphite, add them into a melt spinning machine for spinning, comb the fibers, lay them into a net, and then perform a needle punching process and a hot pressing process to obtain a highly flame-retardant waste spun felt.

[0053] Example 8

[0054] This embodiment provides a production process of highly flame-retardant waste spun felt, comprising the following steps:

[0055] S1, recovering, sorting, and disinfecting nylon waste, and then opening and combing the waste to obtain pretreated fibers;

[0056] S2, immersing 110 parts by weight of the pretreated fiber in 550 parts by weight of an isopropanol solution having a concentration of 90 wt%, adding 40 parts by weight of a chloroacetic acid solution having a concentration of 10 wt%, stirring and reacting at 55° C. for 1 hour, and then washing with deionized water and drying to obtain a modified fiber;

[0057] S3. Evenly mix 100 parts by weight of modified fiber, 10 parts by weight of modified chain extender, 1.5 parts by weight of amino nano-silica and 7 parts by weight of diethylaluminum hypophosphite, add them into a melt spinning machine for spinning, comb the fibers, lay them into a net, and then perform a needle punching process and a hot pressing process to obtain a highly flame-retardant waste spun felt.

[0058] Example 9

[0059] This embodiment provides a production process of highly flame-retardant waste spun felt, comprising the following steps:

[0060] S1, recovering, sorting, and disinfecting nylon waste, and then opening and combing the waste to obtain pretreated fibers;

[0061] S2, immersing 120 parts by weight of the pretreated fiber in 600 parts by weight of a 90 wt% isopropanol solution, adding 60 parts by weight of a 10 wt% chloroacetic acid solution, stirring and reacting at 60° C. for 1.5 h, and then washing with deionized water and drying to obtain a modified fiber;

[0062] S3. Evenly mix 110 parts by weight of modified fiber, 11 parts by weight of modified chain extender, 3 parts by weight of amino nano-silica and 8 parts by weight of diethylaluminum hypophosphite, add them into a melt spinning machine for spinning, comb the fibers, lay them into a net, and then perform a needle punching process and a hot pressing process to obtain a highly flame-retardant waste spun felt.

[0063] Comparative Example 1: Compared with Example 7, no modified chain extender was added, and the rest was the same.

[0064] Comparative Example 2: Compared with Example 7, the modified chain extender was replaced with an equal amount of a commercially available chain extender, and the rest was the same.

[0065] Comparative Example 3: Compared with Example 7, an equal amount of amino nano-silica was replaced by nano-silica, and the rest was the same.

[0066] Performance tests were conducted on Examples 7 to 9 and Comparative Examples 1 to 3. The waste spun felt was made into samples of 50 mm × 300 mm. The breaking strength and breaking elongation were as per GB / T 3923.1-2013. The flame retardant properties were as per GB / T 5454-2008. The limiting oxygen index value was tested. The higher the limiting oxygen index, the better the flame retardant properties. The results are shown in Table 1.

[0067] Table 1

[0068]

[0069]

[0070] It can be seen from Table 1 that the limiting oxygen index of the waste spun felt prepared by the modified chain extender and amino nano-silica in Examples 7-9 is significantly higher than that in Comparative Examples 1-3, and has good flame retardant properties. At the same time, the elongation at break and the breaking strength are greater than those in Comparative Examples 1-3, and have good strength and toughness. In addition, compared with Comparative Examples 1 and 3, Example 7 has a higher limiting oxygen index, indicating that under the synergistic effect of the modified chain extender and amino nano-silica, the waste spun felt has higher flame retardant properties.

[0071] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0072] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A production process for highly flame-retardant waste spun felt, characterized in that: The following steps are involved: S1, recovering, sorting, and disinfecting nylon waste, and then opening and combing the waste to obtain pretreated fibers; S2, immersing the pretreated fiber in a 90wt% isopropanol solution, adding a 10wt% chloroacetic acid solution, stirring and reacting at 50-60°C for 1-1.5h, and then washing with deionized water and drying to obtain a modified fiber; S3. The modified fiber, modified chain extender, amino nano-silica and diethylaluminum hypophosphite are uniformly mixed and added into a melt spinning machine for spinning. After combing and laying into a net, the fibers are needle punched and hot pressed to obtain highly flame-retardant waste spun felt.

2. The production process of a highly flame-retardant waste spun felt according to claim 1, characterized in that: The weight ratio of the pretreated fiber, the isopropanol solution and the chloroacetic acid solution is 100-120:500-600:30-60.

3. The production process of a highly flame-retardant waste spun felt according to claim 1, characterized in that: The weight ratio of the modified fiber, the modified chain extender, the amino nano-silicon dioxide and the diethylaluminum hypophosphite is 90-110:8-11:0.5-3:6-8.

4. The production process of a highly flame-retardant waste spun felt according to claim 1, characterized in that: The modified chain extender is prepared by the following steps: A1. Add 3,4-dihydroxybenzaldehyde to anhydrous methanol, stir and mix, add 1,3-bis(3-aminopropyl)tetramethyldisiloxane alcohol solution dropwise, control the dropping time to 20-30 min, then add glacial acetic acid and anhydrous magnesium sulfate, stir and react for 9-10 h in a nitrogen atmosphere at 60-70° C., cool and place in ice deionized water for precipitation, filter, wash and dry to obtain a silicon-containing Schiff base; A2. Add silicon-containing Schiff base and potassium hydroxide to anhydrous ethanol, stir and mix, add epichlorohydrin, stir and react for 3-4 hours under nitrogen atmosphere and 60-70°C, cool to room temperature, add a 40wt% potassium hydroxide aqueous solution dropwise, control the addition time to 0.5-1h, after the addition is completed, stir and react at 50-60°C for 5-6h, and then post-treat to obtain a modified chain extender.

5. The production process of highly flame-retardant waste spun felt according to claim 4, characterized in that: The dosage ratio of the anhydrous methanol, 3,4-dihydroxybenzaldehyde, 1,3-bis(3-aminopropyl)tetramethyldisiloxane alcohol solution, glacial acetic acid and anhydrous magnesium sulfate is 90mL:4-6g:18-20mL:0.5-1mL:0.6g; the 1,3-bis(3-aminopropyl)tetramethyldisiloxane alcohol solution is prepared by dissolving 1-3mL 1,3-bis(3-aminopropyl)tetramethyldisiloxane in 20mL anhydrous methanol.

6. The production process of highly flame-retardant waste spun felt according to claim 4, characterized in that: The usage ratio of the anhydrous ethanol, the silicon-containing Schiff base, the potassium hydroxide, the epichlorohydrin and the potassium hydroxide aqueous solution is 60 mL: 3-6 g: 0.6 g: 4-8 mL: 4 mL.

7. The production process of highly flame-retardant waste spun felt according to claim 4, characterized in that: The post-treatment is to cool to room temperature, filter using a Buchner funnel, perform rotary evaporation, dissolve in dichloromethane, wash with a saturated sodium carbonate aqueous solution and deionized water in sequence, and then perform rotary evaporation.

8. The production process of a highly flame-retardant waste spun felt according to claim 1, characterized in that: The amino nano silicon dioxide is prepared by the following steps: Add nano-silica to deionized water, ultrasonically disperse for 30 minutes, add 3-aminopropyltriethoxysilane, stir and mix, add PBS buffer to adjust the pH value to 7-8, stir and react at 60-70°C for 10-12 hours, and then centrifuge, wash and dry to obtain amino nano-silica.

9. The production process of highly flame-retardant waste spun felt according to claim 8, characterized in that: The usage ratio of the deionized water, nano silicon dioxide and 3-aminopropyltriethoxysilane is 40 mL: 1-4 g: 1-3 mL.

10. A highly flame-retardant waste spun felt, characterized in that: Prepared according to the production process according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Flame-retardant chain-extending nylon 6 composition and preparation method thereof

    CN103897385A

  • Epoxy type chain extender and preparation method thereof

    CN108484534A

  • Environmental-friendly flame-retardant antibacterial fiberboard for reinforced wood floor

    CN109159243A

  • Schiff-base P-N-Si flame-retardant PA6, fiber and preparation method thereof

    CN110656394A

  • Preparation method of waste textile regenerated packaging composite material

    CN110936641A